Incidence of intensive care unit acquired weakness in critically ill patients treated with kidney replacement therapy: A systematic review and meta-analysis - Tao Yang; Kaikai Zhang; Xiuming Xi; Shanshan Yu (PLoS ONE, 2025)
Background This study assesses the incidence of ICU-acquired weakness (ICUAW) among patients using kidney replacement therapy (KRT) and explores the uncertain relationship between KRT and ICUAW in critically ill adult patients. Methods A comprehensive search was conducted across PubMed, Embase, Web of Science, and the Cochrane Central Register of Controlled Trials up to June 10, 2024. Inclusion criteria encompassed randomized controlled trials (RCTs), as well as prospective and retrospective cohort studies that examined the correlation between KRT and ICUAW in adult ICU patients. Heterogeneity was evaluated using the χ² and I² statistics. Publication bias was assessed qualitatively via funnel plots and quantitatively using Begg’s and Egger’s tests. Results A total of twelve cohort studies involving 2275 adult patients were included, with no RCTs meeting the criteria. The overall incidence of ICUAW was 49.5% in patients using KRT, compared to 34.8% in non-KRT controls. These studies collectively demonstrated a statistically significant association between KRT and a higher incidence of ICUAW (OR, 2.12; 95% CI, 1.34–3.34). Subgroup and sensitivity analyses reinforced this association, particularly in studies involving patients with clinical weakness, large sample sizes, and low risk of bias. However, studies focused on patients with abnormal electrophysiology and small sample sizes did not show this correlation. Despite the substantial findings, statistical heterogeneity was present. No significant publication bias was detected. Conclusion This study highlights a significant association between KRT and an increased incidence of developing ICUAW.